Poverty, inequality, child abuse and neglect: Changing the conversation across the UK in child protection?. (February 2019) - Featherstone, Brid; Morris, Kate; Daniel, Brigid; Bywaters, Paul; Brady, Geraldine; Bunting, Lisa; Mason, Will; Mirza, Nughmana
Abstract: This article explores the evidence on the relationship between poverty, inequality and child abuse and neglect. It argues for the importance of developing further work on the implications of inequality, in particular, as this is a significantly underdeveloped area of study despite compelling evidence of its pertinence to the harms that children and their families experience. Drawing from the findings of a quantitative study that an 'inverse intervention law' appeared to be in operation with systematic unequal implications for children, the conceptual thinking behind a new qualitative study to explore why and how this law operates is explained. The implications for policy and practice are discussed in order to promote further debate about what is often a neglected or invisible aspect of child protection.